2020
DOI: 10.1186/s12891-020-03416-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Spinopelvic sagittal alignment on the surgical outcomes of dropped head syndrome: a multi-center study

Abstract: Background Most of the previous studies about the surgical treatment of dropped head syndrome (DHS) are small case series, and their primary outcome measures were cervical alignment parameters. Therefore, little is known about the associations between pre- and postoperative global sagittal alignment in the whole spine and the clinical outcomes of the surgical treatment of DHS. In this study, we investigated the surgical outcomes of DHS, including correction of cervical and global spinal sagittal alignment. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…4 Regarding surgery for DHS, Kudo et al reported that pre-and postoperative SVA and PI (pelvic incidence)-LL (lumbar lordosis) were associated with surgical outcomes of patients with DHS. 14 The present study could not analyze operative results because of the inclusion of many non-operative cases. However, our results showed that P-DHS represented low C2-C7A and T1 due to loss of thoraco-lumbar compensation, and also that there was a difference between P-and N-DHS concerning the sagittal spinal compensation mechanism.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…4 Regarding surgery for DHS, Kudo et al reported that pre-and postoperative SVA and PI (pelvic incidence)-LL (lumbar lordosis) were associated with surgical outcomes of patients with DHS. 14 The present study could not analyze operative results because of the inclusion of many non-operative cases. However, our results showed that P-DHS represented low C2-C7A and T1 due to loss of thoraco-lumbar compensation, and also that there was a difference between P-and N-DHS concerning the sagittal spinal compensation mechanism.…”
Section: Discussionmentioning
confidence: 94%
“…8 In a recent study, Kudo et al analyzed the poor surgical outcome of DHS and proposed consideration of the global spinopelvic sagittal alignment parameters. 14 The purpose of the present study was to analyze the cervical sagittal alignment of DHS from the point of view of global sagittal spinal alignment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DHS can be classified into three groups based on preoperative radiological parameters; Type 1 (SVA ≤0 mm and PI-LL ≤10°), Type 2 (SVA > 0 mm and PI-LL ≤10°), and Type 3 (PI-LL >10°). [ 5 ] Several surgical strategies for DHS have been reported including; posterior multiple-level fixation or combined anterior and posterior cervical fixation [ Table 2 ]. [ 1 , 2 , 4 , 7 - 9 ] In our two cases of DHS, we chose first to perform posterior cervical facetectomies with pedicle screw application, followed by multilevel ACDF with posterior rod/pedicle/screw fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Hashimoto et al reported that DHS could be classified into two distinct types based on the sagittal vertical axis (SVA) in global alignment: SVA + and SVA− [11]. Other reports suggested that global spine alignment parameters in patients with DHS are related to surgical treatment outcomes [14]. Nonetheless, most previous studies have focused on alignment factors, and few studies have assessed other radiological characteristics in DHS.…”
Section: Introductionmentioning
confidence: 99%